2020
DOI: 10.1111/cas.14533
|View full text |Cite
|
Sign up to set email alerts
|

CENP‐50 is required for papilloma development in the two‐stage skin carcinogenesis model

Abstract: CENP‐50/U is a component of the CENP‐O complex (CENP‐O/P/Q/R/U) and localizes to the centromere throughout the cell cycle. Aberrant expression of CENP‐50/U has been reported in many types of cancers. However, as Cenp‐50/U‐deficient mice die during early embryogenesis, its functions remain poorly understood in vivo. To investigate the role of Cenp‐50/U in skin carcinogenesis, we generated Cenp‐50/U conditional knockout (K14CreER‐Cenp‐50/Ufl/fl) mice and subjected them to the 7,12‐dimethylbenz(a)anthracene (DMBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(77 reference statements)
1
1
0
Order By: Relevance
“…A few studies have linked these proteins with tumors. One study indicated that CENPU was essential for papilloma development in a skin carcinogenesis model (33). In the current study, we found that CENPU was significantly upregulated in the tumor tissues of patients with LUAD.…”
Section: Discussionsupporting
confidence: 62%
“…A few studies have linked these proteins with tumors. One study indicated that CENPU was essential for papilloma development in a skin carcinogenesis model (33). In the current study, we found that CENPU was significantly upregulated in the tumor tissues of patients with LUAD.…”
Section: Discussionsupporting
confidence: 62%
“…The role of various genes and cellular signaling pathways involved in developing skin tumors can be investigated in this two-stage skin carcinogenesis model by using a genetically engineered mouse model [ 10 ]. Genetically modified mice have been used to analyze various genes (i.e., oncogenic transcription factors, constitutive centromere-related network proteins) [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%